UTHM Student Representative Council Program Management System - HERY , MOHAMMAD IQMAL HAKIM; SULAIMAN, RABATUL ADUNI (Applied Information Technology And Computer Science, 2026)
The MPP at UTHM currently relies on manual processes for managing student activities, leading to inefficiencies, data loss, and organizational delays. This study aims to design and develop a web-based Student Program Activity Management System to centralize activity planning, scheduling, execution tracking, and reporting for improved coordination between MPP members, administrators, and students. The system was developed using PHP, MySQL, HTML/CSS, and JavaScript, with systematic testing conducted through 43 test cases and User Acceptance Testing involving 13 respondents across multiple user roles. The results demonstrate 100% system functionality success with 92.3% of users rating the system as excellent, indicating significant improvements in program management efficiency and user satisfaction. The system successfully addresses manual workflow limitations and provides a foundation for future enhancements including notification systems and dynamic role management.